Peningkatan Life Skills Warga Belajar melalui Kursus Komputer di PKBM Cipta Cendekia Kota Tangerang - Trisnawati, Bela; Sudadio, Sudadio; Fauzi, Ahmad (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2017)
The purpose of this study is to know the efforts, outcomes, supporting factors and inhibiting the increase of citizen life skills through computer courses. The research approach used is descriptive qualitative with data obtained from interviews, observation, documentation, written test and practice test. Sources of research data obtained from tutors, study residents, and managers. Data were analyzed using source triangulation, method, and theory. The results showed that the tutor's efforts in improving the computer skills of citizens learning the B and C package run well and successfully. Course participants get results with cognitive, affective and skills skills that help course participants find work and have a business. Supporting factors are the high level of willingness of studying citizens, adequate facilities and infrastructure, media and learning methods are quite good, as well as aid funds from the APBD is quite helpful. Inhibiting factors are lack of recruiting, damaged computers and fewer number of participants, limited allocation of APBD funds, and lack of tutors.